Kesaksian Tunanetra dalam Tindak Perzinaan Perspektif Fikih Jinayah - Akhmad Hanafi Dain Yunta; Rachmat Bin Badani Tempo; Muhammad Fitrah Waila Zamzani (AL-QIBLAH: Jurnal Studi Islam dan Bahasa Arab, 2024)
This research aims to find out about the testimony of the blind in the act of adultery from a jinayah jurisprudence perspective. The type of research used is descriptive qualitative (non-statistical) using the library research method which focuses on the study of manuscripts and texts through juridical, normative and philosophical approaches. The research results found were as follows; First, the concept of testimony in an act of adultery is not the same as testimony in general, the concept of testimony in an act of adultery from a fiqh perspective must be with four Muslim men who are fair, mature, sensible and independent and testimony from women is not accepted, the witnesses give their testimony to a panel in front of a judge explaining the act of adultery and providing information about the time and place where the act of adultery occurred. Second, there is a difference of opinion among the scholars regarding the testimony of the blind in the act of adultery, according to the general opinion, the testimony of the blind in the act of adultery is testimony that is rejected, whereas according to Ibn H}azm, the testimony of the blind can be generally accepted and another history from the Shafi'i school of thought is that allows blind testimony in the act of adultery under certain circumstances. It is hoped that the implications of this research can become material for consideration, literature or reference for the academic world as well as positive reference material and information for society in general.